IMPLEMENTASI METODE PEMBELAJARAN DEMONSTRASI TERHADAP PENINGKATAN HASIL BELAJAR TEKNOLOGI DASAR OTOMOTIF SISWA SMK - Fayi Fachrudin, Muchammad; Erwin, Erwin Komara Mindarta; Komar, Komarudin; Syarif, Syarif Suhartadi (Jurnal Pendidikan Vokasi Otomotif, 2025)
Vocational High School (SMK) is a bridge to create graduates who have expertise in certain fields that are in accordance with the business and industrial world (DU/DI). In this case, SMK must prepare effective learning in all Light Vehicle Engineering (TKR) subjects including basic automotive technology which is the basis of lessons in the Light Vehicle Engineering Department. However, the learning approach used is still conventional so that student grades need to be improved and student motivation also needs to be improved. In connection with this, this study aims to improve student competence using the Demonstration Learning Method at SMKN 6 Malang. in the subject of Basic Automotive Technology. This study applies the Research (Demonstration) method using pre-test, post-test, field notes, and interview guidelines. After two meetings in two cycles. The results in the study were said to have increased because in cycle one the completion of 44.83% of knowledge increased by 100%. The increasing percentage of each cycle is seen from the average cycle one 75 for knowledge for cycle two the average knowledge gets 82.69 so that it exceeds the minimum criterion limit of 75. Student motivation also increases and student perceptions are also positive towards the implementation of demonstration learning. It can be understood that demonstration learning is able to increase the value of knowledge, skills, and student motivation in learning basic automotive technology subjects. Keywords: demonstration learning, basic automotive technology, vocational high school